Branched polyethyleneimine-assisted boronic acid-functionalized magnetic nanoparticles for the selective enrichment of trace glycoproteins. Issue 23 (2nd November 2017) - Li, Daojin; Bie, Zijun
Abstract : Boronate affinity materials, as efficient sorbents for extraction, separation and enrichment of glycoproteins, have attracted more and more attention in recent years. Abstract : Boronate affinity materials, as efficient sorbents for extraction, separation and enrichment of glycoproteins, have attracted more and more attention in recent years. However, conventional boronate affinity materials suffer from low binding affinity due to the use of single boronic acids, which makes the extraction of glycoproteins in trace concentration rather difficult or impossible. Here we present a type of high boronate avidity material, polyethyleneimine (PEI)-assisted boronic acid-functionalized magnetic nanoparticles (MNPs). Branched PEI was used as a scaffold to amplify the number of boronic acid moieties, while 2, 4-difluoro-3-formyl-phenylboronic acid (DFFPBA), exhibiting high affinity and excellent water solubility toward cis -diol-containing compounds, was employed as an affinity ligand. Due to the PEI-assisted synergistic multivalent binding, the boronate avidity MNPs exhibited a high binding affinity toward glycoproteins with dissociation constants of 10 −6 –10 −7 M, which was the highest among the reported boronic acid-functionalized materials that can be applied for a glycoproteomic analysis. Such an avidity enabled the selective extraction of trace glycoproteins as low as 2 × 10 −15 M. This feature greatly favored the selective enrichment of trace glycoproteins from real samples. Meanwhile, the boronate avidity MNPs were tolerant to the interference of abundant sugars. In addition, the PEI-based boronate avidity MNPs exhibited high binding capacity and low binding pH. The feasibility for practical applications was demonstrated with the selective enrichment of trace glycoproteins in human saliva.